The gender gap and the COVID-19 pandemic: An analysis of net Brazilian formal job destruction - Maria Micheliana da Costa Silva; Marcelo Henrique Shinkoda (EconomiA, 2021)
This paper sets out to analyze gender behavior in the Brazilian labor market as a result of the economic effects of the COVID-19 pandemic. It focuses on job destruction and creation during the lockdown and implementation of social distancing throughout 2020. To do so, it uses the New General Register of Employed and Unemployed (NCAGED) and applies the Oaxaca-Blinder decomposition to net male and female job destruction at municipal level, in the 18 to 40 age group. In addition, inequality for every month of 2020, in terms of the pre- and post-pandemic context was verified. It was found that the initial months affected all formal workers but had an even greater effect on women. Another relevant contribution of this study is its inequality decomposition, where the findings show that it is largely due to structural effects.
Keywords: J16; J23; J63; 330; COVID-19 pandemic; Gender Gap; Inequality decomposition; Job Destruction